RENDERING FUNCTION FEATURES OF THE FRENCH COLLOQUIAL INTERROGATIVE CONSTRUCTIONS IN UKRAINIAN FICTION TRANSLATION - Andriy Bilas (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article deals with the problems of colloquial interrogative sentences having the function features in the source and target fiction texts. The importance of the research of interrogative sentences is defined by frequent use of questioning in the process of communication and a close connection of the problem of questioning with other sociolinguistic issues. The given paper outlines function features of the colloquial interrogative sentences on the material of J.-M. Guenassia's "The Incorrigible Optimists Club" and its Ukrainian translation by means of the analysis of possible ways of their rendering into Ukrainian. The author takes into account many works devoted to the study of questioning as a linguistic and translation category, paying special attention to the place of interrogative sentences in the French colloquial speech. The analysis of the colloquial interrogatives functioning in J.-M. Guenassia's novel "The Incorrigible Optimists Club" allows the author to conclude that translation difficulties are caused not so much by their text-functional features, but rather by their structural, semantic, figurative, and socio-functional characteristics, as well as by the asymmetry of the structural elements and register polyphony of the source and target languages.